Teaching Values Through History: Implementation of Indonesia's Pancasila Student Profile in a Remote Papuan Context - Mau, Leni Marlina; Miftahuddin, Miftahuddin (Journal of Innovation and Research in Primary Education, 2025)
This qualitative case study investigated the integration of Pancasila Student Profile values within history education at SMA Negeri Kolese Pendidikan Guru Khas Papua Merauke, a specialized teacher-training institution in Indonesia's remote eastern region. Data were collected through participant observation, semi-structured interviews with school principals, history teachers, and curriculum developers, and documentary analysis of lesson plans, student portfolios, and instructional materials. Findings revealed that deliberate pedagogical strategies—including project-based learning, role play, case studies, and reflective discussions—successfully cultivated mutual cooperation, global diversity, critical reasoning, and nationalism dimensions among students. History education effectively functioned as a character formation vehicle when contextualized within Papua's multicultural reality and linked to contemporary issues. However, independence and creativity dimensions remained underdeveloped due to persistent reliance on teacher direction. Implementation faced significant barriers including insufficient instructional time, resource limitations, transmission-oriented teaching habits, student focus on exam scores rather than character development, and inadequate parental support. The study demonstrates that effective character education in marginalized regions requires curriculum restructuring prioritizing depth over coverage, enhanced teacher professional development, increased resource investment, and systematic family-school collaboration. These findings contribute empirical evidence regarding national character education framework adaptation for diverse sociocultural contexts while advancing theoretical understanding of contextualized character education in remote, underserved educational settings.